2015
DOI: 10.1002/jmr.2473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neohesperidin dihydrochalcone on the activity and stability of alpha‐amylase: a comparative study on bacterial, fungal, and mammalian enzymes

Abstract: Neohesperidin dihydrochalcone (NHDC) was recently introduced as an activator of mammalian alpha-amylase. In the current study, the effect of NHDC has been investigated on bacterial and fungal alpha-amylases. Enzyme assays and kinetic analysis demonstrated the capability of NHDC to significantly activate both tested alpha-amylases. The ligand activation pattern was found to be more similar between the fungal and mammalian enzyme in comparison with the bacterial one. Further, thermostability experiments indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Another study revealed that NHDC inhibited the adipogenic differentiation of human adipose stem cells and prevented the formation of obesity. This may be related to its inhibition of α-amylase activity , and reduction of the abundance of the intestinal bacteria of Prevotella , Purplasomonas , Spironella , Veracinaceae , and Veroncoccus . , Although the antiobesity effect of NHDC was confirmed, , existing studies mainly focused on the inhibitory effect of NHDC on adipose tissue formation. The mechanism by which NHDC ameliorates glycolipid metabolism abnormalities still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that NHDC inhibited the adipogenic differentiation of human adipose stem cells and prevented the formation of obesity. This may be related to its inhibition of α-amylase activity , and reduction of the abundance of the intestinal bacteria of Prevotella , Purplasomonas , Spironella , Veracinaceae , and Veroncoccus . , Although the antiobesity effect of NHDC was confirmed, , existing studies mainly focused on the inhibitory effect of NHDC on adipose tissue formation. The mechanism by which NHDC ameliorates glycolipid metabolism abnormalities still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, an increase in the amount of NHDC results in increased enzyme activity up to three times. K m values were increased at concentrations less than 400 μM NHDC, whereas decreased at higher concentrations 46 …”
Section: Resultsmentioning
confidence: 91%
“…K m values were increased at concentrations less than 400 μM NHDC, whereas decreased at higher concentrations. 46 The activation of an enzyme by a compound can be done by increasing the binding affinity of the substrate to the enzyme or increasing the catalytic constant. 47 Zhang et al reported that lignin can act as an α-amylase activator; the activity ratio increased rapidly with increasing lignin concentrations.…”
Section: Enzyme Inhibitionmentioning
confidence: 99%
“…On the other hand, activators of the enzyme may potentially show an adverse effect in this regard, although hypothetically beneficial for digestive problems. Interestingly, the commercially available sweetener neohesperidin dihydochalcone (from sweet orange), which has a chalcone structural component was found to activate alpha-amylase from different sources [49,50]. Xanthine derivatives, pentoxyfilline, theobromine and caffeine were also found to slightly (20-30%) increase enzyme activity [51].…”
Section: Glucose Homeostasis and Related Metabolic Conditions Disordersmentioning
confidence: 99%